The Association of Some Single Nucleotide Polymorphisms of CYP19A1 Gene with Breast Cancer in Vietnamese Women - Huyen, Pham Thi; Anh, Tran Thi Thuy; Van, Nguyen Thi Hong (VNU Journal of Science: Natural Sciences and Technology; Vol 34 No 4DO - 10.25073/2588-1140/vnunst.4796, 2018)
Abstract: The CYP19A1 gene encoding aromatase P450, a key enzyme in estrogen metabolism, catalyzes the conversion of testosterone to estradiol and androstenedione to estrone. It is generally believed that polymorphisms in genes encoding key enzymes involved in these pathways could affect the activity of enzymes, which can change the level of endogenous hormones. Therefore, genetic polymorphisms in hormone-related genes could increase the breast cancer susceptibility.  In this study, 60 breast cancer women’s blood samples and 50 control blood samples were analyzed to identify the genotype frequencies at SNP loci rs10046 C>T and rs2236722 Trp39Arg (T>C) on CYP19A1 using PCR-RFLP and PCR-CTPP, respectively. The data were analyzed to determine the association between these polymorphism loci and susceptibility to breast cancer. The result shows that, the genotype frequencies at SNP rs10046 in the controls were CC (14%), CT (48%), TT (38%); in the infected group were CC (18.33%), CT (58.33%) and TT (23.34%); and at SNP rs2236722, in the control group: TT (94%), TC (6%); in the infected group: TT (90%), TC (10%). The OR analysis of the gene carrying the CC and TC genotypes compared with TT genotype at both loci (OR=2.01; 95% CI=0.87–4.67 with rs10046 and OR = 1.74; 95%CI= 0.40 – 7.42 with rs2236722) indicated that these SNP loci in CYP19A1 had no effect on breast cancer susceptibility. Keywords: Breast cancer, SNP, rs10046, rs2236722, CYP19A1 gene. References [1] Bora M. T., Tülin Ö., Halil I. K., Sennur I., Calay Z., Oğuz Ö., Turgay I.(2010), “CYP17 (T-34C) and CYP19 (Trp39Arg) Polymorphisms and their Cooperative Effects on Breast Cancer Susceptibility”, In vivo, 24, pp.71–74. [2] Henderson B. E., Ross R., Bernstein L. (1988), “Estrogens as a cause of human cancer: The Richard and Hinda Rosenthal Foundation award lecture”, Cancer Research, 48, pp.246–253. [3] Chen C., Sakoda L. C., Doherty J. A., Loomis M. M., Fish S., Ray R. M. (2008), “Genetic variation in CYP19A1 and risk of breast cancer and brocystic breast conditions among women in Shanghai, China”, Cancer Epidemiology Biomarkers Prevention, 17(12), pp.3457–3466. [4] Dunning A. M., Dowsett M., Healey C. S., Tee L., Luben R. N., Folkerd E., Novik K. L., Kelemen L., Ogata S., Pharoah P. D., Easton D. F., Day N. E., Ponder B. A. (2004), “Polymorphisms associated with circulating sex hormone levels in postmenopausal women”, J. Natl. Cancer Inst., 96(12), pp.936–945. [5] Hirose K., Matsuo K., Toyama T.(2004), “The CYP19 gene codon 39 Trp/Arg polymorphism increases breast cancer risk in subsets of premenopausal Japanese”, Cancer Epidemiol BiomarkPrev, 13, pp.1407–1411. [6] Kristensen V. N., Harada N., Yoshimura N., Haraldsen E., Lonning P. E. (2000), “Genetic variants of CYP19 (aromatase) and breast cancer risk”, Oncogene, 19, pp.1329–1333. [7] Lunardi G., Piccioli P., Bruzzi P., Notaro R., Lastraioli S., Serra M. (2013), “Plasma estrone sulfate concentrations and genetic variation at the CYP19A1 locus in postmenopausal women with early breast cancer treated with letrozole”, Breast Cancer Research and Treatment, 137(1), pp.167–174. [8] Miyoshi Y., Iwao K., Ikeda N., Egawa C., Noguchi S., (2000), “Breast cancer risk associated with polymorphism in CYP19 in Japanese women”, Int J Cancer, 89, pp.325–328. [9] Pineda B., García-Pérez M.Á., Cano A., Lluch A., Eroles P. (2013), “Associations between Aromatase CYP19 rs10046 Polymorphism and Breast Cancer Risk: From a Case–Control to a Meta–Analysis of 20.098 Subjects”, PLos One, 8(1), pp.1–9. [10] Farzaneh F., Noghabaei G., Barouti E., Pouresmaili F., Jamshidi J., Fazeli A. (2016), “Analysis of CYP17, CYP19 and CYP1A1 gene polymorphisms in Iranian women with breast cancer”, Asian Pacific Journal of Cancer Prevention, 17, pp.23–26. [11] Yang L., Wang X. Y., Li Y. T., Wang H. L., Wu T., Wang B. (2015), “CYP19 gene polymorphisms and the susceptibility to breast cancer in Xinjiang Uigur women”, Genetics and Molecular Research, 14(3), pp.8473–8482. [12] Samson M., Rama R., Swaminathan R., Sridevi V., Nancy K. N., Rajkumar T., (2009), “CYP17 (T-34C), CYP19 (Trp39Arg), and FGFR2 (C-906T) polymorphisms and the risk of breast cancer in South Indian women”, Asian Pacific J Cancer Prev, 10, pp.111–116. [13] Yoshimoto N., Nishiyama T., Toyama T., Takahashi S., Shiraki N., Sugiura H., (2011), “Genetic and environmental predictors, endogenous hormones and growth factors, and risk of estrogen receptor positive breast cancer in Japanese women”, Cancer Science, 102(11), pp.2065–2072. [14] Zins K., Mogg M., Schneeberger C., Abraham D., (2014), “Analysis of the rs10046 polymorphism of aromatase (CYP19) in premenopausal onset of human breast cancer”, International Journal of Molecular Sciences, 15(1), pp.712–724. [15] Ghisari M., Eiberg H., Long M. (2014), “Polymorphisms in phase I and phase II genes and breast cancer risk and relations to persistent organic pollutant exposure: A case-control study in Inuit women”, Environmental Health, 13(1), pp.19. [16] Ralph D. A., Zhao L. P., Aston C. E., Manjeshwar S., Pugh T. W. (2007), “Age-specific association of steroid hormone pathway gene polymorphisms with breast cancer risk”, Cancer, 109, pp.1940–1948.